Risk Factors and Clinical Outcomes of Non-Curative Resection in Patients with Early Gastric Cancer Treated with Endoscopic Submucosal Dissection: A Retrospective Multicenter Study in Korea - Si Hyung Lee; Min Cheol Kim; Seong Woo Jeon; Kang Nyeong Lee; Jong Jae Park; Su Jin Hong (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims The purpose of this study was to investigate the risk factors and long-term clinical outcomes of non-curative resection (NCR) in a large-scale patient population. Methods We retrospectively analyzed the clinical data of 3,094 patients who underwent endoscopic submucosal dissection (ESD) of early gastric cancer from March 2005 to March 2018 at 13 institutions in Korea. We analyzed the risk factors for NCR and the survival between patients with curative resection and those with NCR with no additional treatment. Results The NCR rate was 21.4% (661/3,094). In multivariate regression analysis, the risk factors affecting NCR with ESD were old age, undifferentiated tumor, tumor location in the upper body, tumor size ≥2 cm, and presence of an ulcer. In Cox proportional hazard regression analysis, tumor size ≥2 cm, submucosal invasion, positive horizontal margin, and lymphovascular invasion were risk factors for local recurrence. In Kaplan-Meier analysis, there was no statistically significant difference in the overall survival between the two groups (log-rank p=0.788). However, disease-specific survival was significantly lower in the NCR group (log-rank p=0.038). Conclusions Clinicians should be aware of the risk factors for NCR and local recurrence after ESD for early gastric cancer, and should consider providing additional treatment after NCR.